Analisis Tata Kelola Sistem Informasi Dengan Framework COBIT-5: Studi Kasus Pada PT. Batu Karang - Raissa Amanda Putri; Fadhlan Hussaini Srg; Sinta Dewi; Tania Yulindra; Wahyu Herlambang (Program Studi Sistem Informasi, 2020)
Information systems governance is the structure of relationships and processes to direct and control an organization to achieve its goals by adding value when balancing risks compared to Information Technology and its processes. Currently, the information system governance process has not been fully implemented by the company. The research produces recommendations for information system governance, which are the development of information system governance that has been implemented by the company. The purpose of making recommendations for information system governance is to improve the performance of the existing system at PT. Batu Karang, where the performance activities are the responsibility of the manager. In this study, there are two domains taken from COBIT, namely EDM05 and APO04. The domain was chosen based on the vision, management, mission and future challenges of PT. Batu Karang. Keywords: it governance, cobit, information, system